Veterinary diagnostics in India: A perspective - K, Nachimuthu; G, Dhinakar Raj (The Indian Journal of Animal Sciences, 2005)
The various assay formats that lend themselves for development into ’on-site’ diagnostic kits have briefly elucidated. These include the dot-ELISA, latex agglutination tests, Lateral flow and flow through tests. Immunochromatographic assays also called ’lateral flow tests’ or simply strip tests are the test of choice in future largely due to their user-friendly format, quick results, long-term stability of reagents and being relatively inexpensive to make. These features make strip tests ideal for rapid point of care testing on the clinician’s table. The status of the diagnostics in lndia had been evaluated, and some remedial measures to be undertaken for improvement of the qualily of veterinary diagnostics in lndia have also been suggested.